ANALYSIS OF THE FACTORS INFLUENCING DOMESTIC INVESTMENT IN INDONESIA FROM 1990 TO 2019 - Meliya Putri Asdiyana (Transpublika Publisher, 2022)
Domestic investment is essentially the first step in economic development activities, which is a very important component in contributing to domestic national income. This study aims to analyze the effect of inflation, credit interest rates, labor and the IDR/US exchange rate on domestic investment in Indonesia. This study uses the ECM econometric analysis method to determine the factors that influence domestic investment in Indonesia. Econometric analysis shows that inflation, credit interest rates, the IDR/US exchange rate, and labor are significant to domestic investment in Indonesia. The advice given in this research is that the government should provide the development of an integrated system such as education, skills training that is commensurate with the needs of the labor market. Since the availability of a number of qualified workers will further increase the fighting power in increasing production capacity which can further increase investor interest in investing in the country and the government should anticipate the low exchange rate with a revaluation policy, namely the policy of increasing the domestic exchange rate against foreign exchange rates.